Ipomoea batatas L. and Anti-Inflammation Effect: A Systematic Review Its Therapeutic Role in Rodent Models: Ipomoea batatas L. for Rodent Anti-Inflammation - Utami, Fista; Amalia, Diva; Juherman , Yulia Novika; Kusma Ristanti, Idcha; Prabandari , Yunilla (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This systematic review aims to evaluate the health benefits of Purple Sweet Potato (PSP) contain anthocyanins, phenolic acids, and flavonoids in animal models, focusing on its antioxidant, anti-inflammatory, lipid peroxidation, and immunomodulatory properties. Owing to its increasing scientific significance, investigating its health effects in animal models offers important insights into its potential therapeutic applications for human health. Fourteen eligible in vivo studies were identified from 5.043 original research articles following predefined eligibility criteria based on population, intervention, comparison, outcome, and study design (PICOS). These studies employed various extracts (aqueous, ethanolic, methanolic, fermented) and animal models (Wistar rats, BALB/c mice, Kunming mice, Sprague-Dawley rats) to investigate the effects. The PSP significantly reduced oxidative stress markers such as Malondialdehyde (MDA) and enhancing endogenous antioxidant enzymes including Superoxide Dismutase (SOD), Glutathione Peroxidase (GPx), and Catalase (CAT). Anti-inflammatory effects were evident through downregulation of Tumor Necrosis Factor-Alpha (TNF-α), Interleukin-1 Beta (IL-1β), Interleukin-6 (IL-6), Nitric Oxide (NO), and Matrix Metalloproteinase-3 (MMP-3), mediated via suppression of Nuclear Factor Kappa B (NF-κB) and Mitogen-Activated Protein Kinase (MAPK). Anti-inflammatory effects were observed in high-fat diet-induced obese rats, where PSP supplementation (5% weight/weight, w/w) markedly reduced TNF-α, IL-6, Monocyte Chemoattractant Protein-1 (MCP-1), and Interleukin-1 Beta (IL-1β) in adipose tissue. Significant enhancement of endogenous antioxidants occurred in arthritic rats, with PSP extracts (300 mg/kg BW) increasing CAT, Peroxidase (POD), and SOD while lowering IL-1β, IL-6, and NO. The lipid peroxidation reduction was seen in Carbon Tetrachloride (CCl₄)-induced liver injury, where anthocyanin-rich PSP extract (400 mg/kg BW) decreased MDA, increased SOD and Glutathione (GSH). Long-term intervention and aqueous-fermented extracts are particularly promising due to their safety profiles and suitability for functional food formulations, but heterogeneity in dosages and durations limits cross-study comparability. Future research should emphasize clinical trials to establish safety, efficacy, and translational relevance in human health.